Extension of the Period for Payment of Quota Increase Under the Fourteenth General Review of Quotas. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2016)
This paper proposes a 30-day extension of the initial period for payments to increase quotas under the Fourteenth General Review of Quotas ('Fourteenth Review') through March 28, 2016. Under Board of Governors Resolution No. 66-2, each member shall pay to the Fund the increase in its quota within 30 days after the later of (a) the date on which it notifies the Fund of its consent, or (b) the date on which all of the general effectiveness conditions for the quota increases under the Fourteenth Review are met, provided that the Executive Board may extend the payment period as it may determine.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet